Tracker - Paulsen, Gary. (Scarsdale, N.Y. : Bradbury Press, 1984)
Only thirteen, John must track a deer in the Minnesota woods for his family's winter meat, and in doing so finds himself drawn to the doe who leads him and hating his role as hunter.
G9
Keywords: Hunting -- Fiction; Deer -- Fiction; Minnesota -- Fiction